Adverse childhood experiences and frequent insufficient sleep in 5 U.S. States, 2009: a retrospective cohort study - Chapman, Daniel P (BioMed Central, 2013)
BACKGROUND: Although adverse childhood experiences (ACEs) have previously been demonstrated to be adversely associated with a variety of health outcomes in adulthood, their specific association with sleep among adults has not been examined. To better address this issue, this study examines the relationship between eight self-reported ACEs and frequent insufficient sleep among community-dwelling adults residing in 5 U.S. states in 2009. METHODS: To assess whether ACEs were associated with frequent insufficient sleep (respondent did not get sufficient rest or sleep ≥14 days in past 30 days) in adulthood, we analyzed ACE data collected in the 2009 Behavioral Risk Factor Surveillance System, a random-digit-dialed telephone survey in Arkansas, Louisiana, New Mexico, Tennessee, and Washington. ACEs included physical abuse, sexual abuse, verbal abuse, household mental illness, incarcerated household members, household substance abuse, parental separation/divorce, and witnessing domestic violence before age 18. Smoking status and frequent mental distress (FMD) (≥14 days in past 30 days when self-perceived mental health was not good) were assessed as potential mediators in multivariate logistic regression analyses of frequent insufficient sleep by ACEs adjusted for race/ethnicity, gender, education, and body mass index. RESULTS: Overall, 28.8% of 25,810 respondents reported frequent insufficient sleep, 18.8% were current smokers, 10.8% reported frequent mental distress, 59.5% percent reported ≥1 ACE, and 8.7% reported ≥ 5 ACEs. Each ACE was associated with frequent insufficient sleep in multivariate analyses. Odds of frequent insufficient sleep were 2.5 (95% CI, 2.1-3.1) times higher in persons with ≥5 ACEs compared to those with no ACEs. Most relationships were modestly attenuated by smoking and FMD, but remained significant. CONCLUSIONS: Childhood exposures to eight indicators of child maltreatment and household dysfunction were significantly associated with frequent insufficient sleep during adulthood in this population. ACEs could be potential indicators promoting further investigation of sleep insufficiency, along with consideration of FMD and smoking.